MYOCARDITIS AFTER COVID-19 M-RNA VACCINATION : A SYSTEMATIC REVIEW - Frida Setiawan, Yenny (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
One of the possible solutions to the problem of COVID-19 is vaccination against the virus. Vaccination may provide immunity by stimulating the immune system of the receiver to mount a response to the antigens that are present inside the vaccine. As part of the immunological response, a person may have both local and systemic symptoms, such as discomfort at the injection site or fever. Additional components of the vaccination have the potential to cause responses. Myocarditis that was reported to VAERS after vaccination with mRNA-based COVID-19 had demographic characteristics that were comparable to those of cases of myocarditis that were not associated with vaccination. However, the acute clinical course of myocarditis that was reported to VAERS after vaccination was different from the acute clinical course of myocarditis that was reported in cases that were not associated with vaccination. The risk of myocarditis increased after getting immunizations based on mRNA for COVID-19 in all age and gender groups, with the risk being highest after the second immunization dose in male adolescents and young men. This danger has to be assessed in light of the many positive aspects associated with the COVID-19 vaccination. One of the many possible processes is a hyperimmune or inflammatory response after exposure to spike protein, mRNA strand, or an unexplained trigger. Another possibility is a delayed onset of hypersensitivity.